Systematic Literature Review: The Role of School Strategic Plans in Improving Educational Quality - Dexulear Mexi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study investigates the role of school strategic plans in enhancing educational quality, moving beyond their perception as mere administrative requirements. A systematic literature review (SLR) was conducted, analysing 15 peer-reviewed articles published between 2021 and 2026. The findings reveal that effective strategic planning contributes to quality improvement through three key mechanisms: (1) structured formulation processes involving stakeholder deliberation, (2) alignment of resources with institutional vision and mission, and (3) systematic monitoring and evaluation. However, the review also identifies persistent challenges, including limited technological integration, insufficient professional development, and a tendency toward administrative compliance rather than pedagogical transformation. This study contributes a synthesized framework that conceptualizes strategic plans as “living roadmaps” for institutional change, emphasizing the synergy between managerial leadership and active document engagement. The findings provide actionable insights for school principals and policymakers seeking to bridge the gap between long-term vision and daily operational practice.